2007
DOI: 10.1016/j.jvs.2007.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Postthrombotic or non-postthrombotic severe venous insufficiency: Impact of removal of superficial venous reflux with or without subcutaneous fasciotomy

Abstract: Patients with severe chronic venous insufficiency with therapy-resistant or recurrent ulcer disease due to deep and superficial insufficiency have higher i.m. tissue pressures than patients with only superficial venous reflux, even though both groups have higher i.m. and s.c. tissue pressures compared with normal values. Eradication of all superficial reflux lowers s.c. tissue pressure, while additional fasciotomy lowers both i.m. and s.c. tissue pressures and increases TcPO(2), which seems to promote ulcer he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…Several clinical trials have demonstrated that surgery performed to eradicate venous reflux in superficial veins notably reduced the recurrence rate of ulcers in a follow-up period of up to 3 years (Barwell et al, 2000; Zamboni et al, 2003; Barwell et al, 2004). Furthermore, as tissue pressures are increased in the affected limbs of patients with PTS, the role of fasciotomy in addition to surgical correction of superficial venous reflux was evaluated in a small study for the treatment of venous ulcers (Christenson, 2007). The addition of fasciotomy promoted healing in 11 out of 12 ulcers (92%), compared to only four out of 11 (36%) ulcers treated with surgical correction of superficial venous reflux alone (p=0.049) (Christenson, 2007).…”
Section: Treatment Of Ptsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical trials have demonstrated that surgery performed to eradicate venous reflux in superficial veins notably reduced the recurrence rate of ulcers in a follow-up period of up to 3 years (Barwell et al, 2000; Zamboni et al, 2003; Barwell et al, 2004). Furthermore, as tissue pressures are increased in the affected limbs of patients with PTS, the role of fasciotomy in addition to surgical correction of superficial venous reflux was evaluated in a small study for the treatment of venous ulcers (Christenson, 2007). The addition of fasciotomy promoted healing in 11 out of 12 ulcers (92%), compared to only four out of 11 (36%) ulcers treated with surgical correction of superficial venous reflux alone (p=0.049) (Christenson, 2007).…”
Section: Treatment Of Ptsmentioning
confidence: 99%
“…Furthermore, as tissue pressures are increased in the affected limbs of patients with PTS, the role of fasciotomy in addition to surgical correction of superficial venous reflux was evaluated in a small study for the treatment of venous ulcers (Christenson, 2007). The addition of fasciotomy promoted healing in 11 out of 12 ulcers (92%), compared to only four out of 11 (36%) ulcers treated with surgical correction of superficial venous reflux alone (p=0.049) (Christenson, 2007). …”
Section: Treatment Of Ptsmentioning
confidence: 99%
“…8 In chronic venous insufficiency, releasing the subcutaneous fluid by subcutaneous fasciotomy decreases the subcutaneous pressure. 9 The same principle is applied in the management of cellulitis. Early superficial subcutaneous fasciotomy in cellulitis can prevent the local complication like skin necrosis and progression to necrotising soft tissue infection.…”
Section: Study Backgroundmentioning
confidence: 99%
“…Neglen and associates have combined iliofemoral stenting with obliteration of superficial venous reflux and found that it is safe, effective and minimally invasive single-stage procedure [34]. Ablation of superficial venous reflux along with subcutaneous fasciotomy for chronic and recurrent venous ulcers improves ulcer healing or success of skin grafting [35]. …”
Section: Interventions To Correct Venous Refluxmentioning
confidence: 99%